Pathologic Doppler velocimetry and correlation with short term perinatal prognosis - Huerta, Igor (2015)
Objectives: To determine both morbidity and mortality in fetuses with pathological Doppler velocimetry and short term handicap. Design: Retrospective, observational, analytical, correlation study. Setting: Fetal surveillance unit, Hospital Nacional Edgardo Rebagliati Martins, Red Asistencial Rebagliati, EsSalud, Lima, Peru. Participants: Pregnant women with pathological Doppler velocimetry and their perinates. Interventions: All pregnant women with altered Doppler velocimetry between February 2008 and February 2010 were studied. They were grouped by Doppler velocimetry types, and frequency of pathology; perinatal morbidity and mortality were determined and correlated with gestational age. SPSS 11,0 was used for statistical analysis, chi square test for discrete variables and Kruskal-Wallis test for continued variables. Significant value was p < ,005. Main outcome measures: Perinatal morbidity and mortality, motor, hearing and psychomotor discapacities at 6 months after birth. Results: Sixty-three pregnant women fulfilled inclusion criteria. Their mean newborns weight was 1 593 g; 24 cases (40%) presented weight at birth less than 10th percentile for gestational age. Most of them showed type III Doppler velocimetry, 46 with signs of hemodynamic redistribution. Global mortality was 8%. Four fetuses died in utero; 59 fetuses (94%) were born alive and only one case died during the study period. Mortality rate was significantly higher and birth weight less in type IV Doppler velocimetry fetuses, mean weight 937 g. Mortality was significatively higher at 24-27,6 weeks. ICU stay, need of assisted ventilation and continuous positive pressure, risk to develop retinopathy and interventricular hemorrhage, and hearing and psychomotor discapacities correlated with prematurity. Conclusions: Doppler velocimetry fetuses with severe hemodynamic compromise presented acidemia and high mortality rate, independent of growth percentile. Intrauterine mortality was significantly associated with Doppler velocimetry severity changes. To continue pregnancy with type III or IV Doppler velocimetry is not recommended in fetuses with lung maturity.